PENGARUH MEMBACA INTENSIF TEKS EKSPOSISI BERBASIS HOTS TERHADAP KEMAMPUAN BERPIKIR KRITIS - Gugun Gunawan (Universitas Negeri Makassar, 2026)
This study aimed to analyze the effect of intensive reading activities of HOTS-based exposition texts on students' critical thinking skills. This study used a quantitative approach with an experimental method. The design of this study was a true experimental design in the form of a pretest-posttest control group design. The study population was all students of MIN 1 Bogor Regency, and samples were selected using a simple random sampling technique. Therefore, 23 students were selected in the experimental class and 24 students in the control class. Data were collected through observation of learning activities and HOTS-based tests to measure critical thinking skills before and after the tests. The test instrument was tested for validity and reliability before use. Data were analyzed statistically through descriptive analysis, prerequisite tests (normality and homogeneity), and hypothesis testing using an independent sample t-test. The results showed that there was a significant difference between the average posttest scores of the experimental class (83.78) and the control class (76.19). The results of the hypothesis test showed a significance value of 0.001 (<0.05), indicating that the application of intensive reading of HOTS-based exposition texts had a significant effect on improving students' critical thinking skills. These findings confirm that repeated reading and systematic text exploration effectively activate students' higher-order cognitive processes.